Dynamic Response and Perturbation Design of Surrounding Rock in Blasting Construction of Small Radius Spiral Tunnel. Issue 5 (October 2020) - Fang, Z B; Yan, Q; Sun, X D; Fu, D; Zhang, X X; Liu, X; Qi, N
Abstract: To achieve a better blasting effect of ultra-long and deep buried spiral tunnel with a small radius, it is necessary to study the dynamic response and disturbance of blasting construction. As the engineering background with a poor engineering geological condition, this paper uses the Midi spiral-tunnel in Yunnan province that has a small radius of curvature, a large burial depth, and a large excavation distance. The blasting load is determined first by calculation. Under different blasting construction parameters, the deformation and dynamic vibration responses of the surrounding rocks are studied using the finite element numerical method. The damage mechanism of rock under the blasting load is analyzed. The tunnel engineering blasting is designed and calculated, and the small distance disturbance design of spiral tunnel blasting construction with a small radius is performed from the excavation method and blasting parameters. The results serve as a reference to reveal the surrounding rock dynamics in blasting construction of the spiral tunnel with a small radius.